Hubungan Paritas Ibu Bersalin Dengan Kejadian Persalinan Kala I Memanjang Di Puskesmas Baamang I Tahun 2020 - agus mulyadi (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2022)
ABSTRACT Background : The first stage is said to be prolonged if it has lasted more than 24 hours in primiparas and 18 hours in multiparas. A latent phase that exceeds 20 hours in primigravida or 14 hours in multiparas is an abnormal condition. An active phase in multiparas lasting more than 6 hours (mean 2,5 hours) and continued cervical dilatation of less than 1,5 cm in hours is an abnormal condition. Based on data at public health center Baaamang I 2020, of the 608 mothers who gave birth, there were 21 mothers who experienced prolonged labot in the first stage, (Pillitteri, 2013). Research Objectives : Knowing the relationship between maternal parity and the incidence of prolonged first stage of labor at public health center Baamang I 2020. Methods : This study uses a retrospective analytic method with a cross sectional research design.conducted at public health center Baamang I in 2020 with a sample of 21 people using a total sampling technique from secondary data. Independent variable parity and dependent variable first stage of labor is prolonged. Results : The results of the analysis using the chi square tets of 21 parity respondents with 11 primiparas (52,4%), 10 multiparas (47,6%), and 0 grandemultiparas (0%). While the first stage extends the latent phase of 3 people (14,3%), and stage 1 st extends the active phase of 18 people (85,7%). There is no significant relationship between parity and prolonged first stage of labor because the p value = 1.000 (>0,05). Conclusion : There is no significant relationship between maternal parity and the incidence of prolonged first stage of labor at public health center Baamang I 2020. Keywords : Parity, first stage, labor.